THE RELATIONSHIP OF KNOWLEDGE AND ATTITUDE OF ELDERLY TO HYPERTENSION INCIDENCE IN TAPIAN DOLOK HEALTH CENTER TAPIAN DOLOK DISTRICT SIMALUNGUN DISTRICT PERIOD - Wilson Samosir; Yulia Delfahedah; Mustaruddin (International Conference on Health Science, Green Economics, Educational Review and Technology, 2021)
Hypertension in the elderly is mostly isolated systolic hypertension (HST), increased systolic pressure causes a greater likelihood of stroke and myocardial infarction even though the diastolic pressure is within normal limits (isolated systolic hypertension). Isolated systolic hypertension is the most common form of hypertension in the elderly. In one study, hypertension occupied 87% of cases in people aged 50 to 59 years. According to the World Health Organization, the elderly are grouped into: middle age, which is the age group of 45 -59 years. Elderly (Elderly): between 60-74 years, Old (Old): between 75-90 years, and very old (Very Old) over 90 years, the research method used is " Analytical with cross sectional design using primary data through a questionnaire based on the knowledge and attitudes of the elderly. The sampling technique in this study was random sampling, namely the researcher determined the sample taken because of certain considerations. From the results of this study it was concluded that there was a relationship between the knowledge of the elderly and the incidence of hypertension at the Tapian dolok Health Center, Simalungun Regency. 2016, this is evidenced by the results of the chi-square test with a p-value = 0.004.